The Decision of Farmers do Fermentation to Increase the Quality of Cocoa Beans in Central Sulawesi Indonesia - Effendy Effendy; Made Antara; Rustam Abdul Rauf; Dance Tangkesalu; Christoporus Christoporus; M. Fardhal Pratama; Muhammad Basir-Cyio; Mahfudz Mahfudz; Muhardi Muhardi (International Journal of Supply Chain Management, 2019)
The fermentation of cocoa beans is an important part of cocoa processing. Fermentation of cocoa beans increases the quality and price of the beans and the resultant cocoa. Although the fermentation of cocoa beans can increase the quality and income of cocoa farming, few farmers in Indonesia implement this fermentation process. This research therefore, focuses on the way Indonesian farmers assess whether or not to ferment their cocoa beans. A total of 284 cocoa farmers were sampled in Central Sulawesi Indonesia. The results showed that out of the more than 50% of farmers who did not ferment their cocoa beans, a majority were simply not interested in increasing the quality of the resultant cocoa. The quality of cocoa beans produced from smallholder plantations, therefore, was continually poor. The decision of cocoa farmers to ferment their cocoa beans, meanwhile, was significantly affected by the gender, age and education level of the head of the household, the number of productive family members, the quantity of cocoa bean production, and the resultant price of the fermented cocoa beans in the market. The resultant price of the fermented cocoa was the most dominant factor.